Characterization of porous solids VI : proceedings of the 6th International Symposium on the Characterization of Porous Solids (COPS-VI), Alicante, Spain, May 8-11, 2002 /: proceedings of the 6th International Symposium on the Characterization of Porous Solids (COPS-VI), Alicante, Spain, May 8-11, 2002. (2002) - Unknown
No abstract available